ANALISIS PENGARUH RASIO KEUANGAN TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN REAL ESTATE DAN PROPERTY DI BURSA EFEK INDONESIA (Students' Journal of Accounting and Banking, 2014)
This study was conducted to test and analyze the influence of the Current Ratio, Total Asset Turnover, Gross Profit Margin, Net Profit Margin, Return on Equity, Debt to Equity Ratio effect on profit growth in the real estate and property companies listed on the Stock Exchange in 2010-2012. The population used is a real estate company that went public on the Stock Exchange in 2010-2012, the number of samples by using purposive sampling technique was about 132 companies. Types of data used are secondary data , such as financial statement data in 2010-2011 and ICMD. The data analysis technique used is multiple linear regression. Normality test indicates that the data are normally distributed research. Test multicollinearity, heteroscedasticity test and autocorrelation test in the classical assumption that the variable was not found to deviate. The results showed that the CR, GPM, ROE variable and DER significant positive effect on profit growth, while TAT and NPM showed no significant effect on profit growth. GPM variable has a significant negative effect on profit growth.Keywords: Current Ratio, Total Asset Turnover, Gross Profit Margin, Net Profit Margin, Return on Equity, Debt to Equity Ratio and Profit Growth